2007
DOI: 10.1177/00238309070500020301
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Syntactic Complexity in Spontaneous Spoken Swedish

Abstract: Hesitation disfluencies after phonetically prominent stranded function words are thought to reflect the cognitive coding of complex structures. Speech fragments following the Swedish function word att 'that' were analyzed syntactically, and divided into two groups: one with att in disfluent contexts, and the other with att in fluent contexts. Complexity was calculated in terms of a number of measures related to syntactic tree structures produced by the analysis tool GRAMMAL. Results showed that disfluent att i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…A thorough conceptual and historical overview of readability research can be found in Vajjala (2015, §2.2). The last decade has seen a rise in research on readability classification, primarily focused on English, but also including French, German, Italian, Portuguese, and Swedish (Roll et al, 2007;Vor der Brück et al, 2008;Aluisio et al, 2010;Francois and Watrin, 2011;Dell'Orletta et al, 2011;Hancke et al, 2012;Pilán et al, 2015). Broadly speaking, these languages have limited morphology in comparison with Russian, which has relatively rich morphology among major world languages.…”
Section: Introductionmentioning
confidence: 99%
“…A thorough conceptual and historical overview of readability research can be found in Vajjala (2015, §2.2). The last decade has seen a rise in research on readability classification, primarily focused on English, but also including French, German, Italian, Portuguese, and Swedish (Roll et al, 2007;Vor der Brück et al, 2008;Aluisio et al, 2010;Francois and Watrin, 2011;Dell'Orletta et al, 2011;Hancke et al, 2012;Pilán et al, 2015). Broadly speaking, these languages have limited morphology in comparison with Russian, which has relatively rich morphology among major world languages.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, several attempts have been made to operationalize this concept in an objective way [28–31]. Various measures have been proposed, ranging from using pure length (as in the number of syllables, words, or intonation units) of an utterance as a proxy for syntactic complexity to fully fledged in-depth analyses of syntactic tree structures [31].…”
Section: Syntactic Complexity Cognitive Load and Speech Understamentioning
confidence: 99%
“…Various measures have been proposed, ranging from using pure length (as in the number of syllables, words, or intonation units) of an utterance as a proxy for syntactic complexity to fully fledged in-depth analyses of syntactic tree structures [31]. Although the first approach has the advantage of being readily available, involving no additional structural analysis, it has been shown at many occasions that increased sentence length does not necessarily go hand in hand with increased syntactic complexity.…”
Section: Syntactic Complexity Cognitive Load and Speech Understamentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature reveals that different studies have used different units for analysis (Budd, 1988;Distefano and Valencia, 1980;Andoline, 1980;Bardovi-Harlig and Bofman 1988;Bardovi-Harlig, 1992;Hosseinchary andYosefy 1387/2008;Samim-Banihashemi 1371Frid, Horne, and Roll 2007;Rashidi and Shahballa 2010). The present study has focused on idea units and main ideas.…”
Section: Units Of Analysismentioning
confidence: 99%